Optimize Household Waste Management - Yunita Rakhmawati; Umi Fitriyati; Ajeng Daniarsih; Farid Akhsani; Wachidah Hayuana; Zahra Firdaus (Community Development Journal, 2023)
Based on data from the Ministry of Environment and Forestry in 2021, household and food waste production in Indonesia is the highest. This waste has not been utilized optimally because the habit of the Indonesian people in sorting waste is still low. Meanwhile, organic waste derived from food waste can be used as liquid organic fertilizer. Liquid organic fertilizers are more practical and easily absorbed by plants. This community service activity aims to improve students' knowledge and skills in making liquid organic fertilizers. The method used is counseling, demonstration, and training on making LOF involving class XI students of SMAN 8 Malang. This activity results in the increased knowledge and skills of students in manufacturing LOFs. In general, this service activity went smoothly. The suggestion for the next activity was to develop a type of LOF from specific materials based on its largest constituent element so that this LOF will be easier to apply according to to plant needs.